Structural and Signaling Events Driving Aspergillus fumigatus-Induced Human Eosinophil Extracellular Trap Release - Barroso, Marina Valente; Gropillo, Isabella; Detoni, Marcella A. A.; Thompson-Souza, Glaucia A.; Muniz, Valdirene S.; Vasconcelos, Claudia Regina Isaías; Figueiredo, Rodrigo T.; Melo, Rossana C. N.; Neves, Josiane S. (Frontiers in Microbiology, 2021)
Eosinophils are granulocytes classically involved in allergic diseases and in the host immune responses to helminths, fungi, bacteria and viruses. The release of extracellular DNA traps by leukocytes is an important mechanism of the innate immune response to pathogens in various infectious conditions, including fungal infections. Aspergillus fumigatus is an opportunistic fungus responsible for allergic bronchopulmonary aspergillosis (ABPA), a pulmonary disease marked by prominent eosinophilic inflammation. Previously, we demonstrated that isolated human eosinophils release extracellular DNA traps (eosinophil extracellular traps; EETs) when stimulated by A. fumigatus in vitro. This release occurs through a lytic nonoxidative mechanism that involves CD11b and Syk tyrosine kinase. In this work, we unraveled different intracellular mechanisms that drive the release of extracellular DNA traps by A. fumigatus-stimulated eosinophils. Ultrastructurally, we originally observed that A. fumigatus-stimulated eosinophils present typical signs of extracellular DNA trap cell death (ETosis) with the nuclei losing both their shape (delobulation) and the euchromatin/heterochromatin distinction, followed by rupture of the nuclear envelope and EETs release. We also found that by targeting class I PI3K, and more specifically PI3Kδ, the release of extracellular DNA traps induced by A. fumigatus is inhibited. We also demonstrated that A. fumigatus-induced EETs release depends on the Src family, Akt, calcium and p38 MAPK signaling pathways in a process in which fungal viability is dispensable. Interestingly, we showed that A. fumigatus-induced EETs release occurs in a mechanism independent of PAD4 histone citrullination. These findings may contribute to a better understanding of the mechanisms that underlie EETs release in response to A. fumigatus, which may lead to better knowledge of ABPA pathophysiology and treatment.